Methodological Complexity: A Both/And Approach to Address Tool Validity and Reliability for Assessment of Cultural Responsiveness in Indigenous Serving Schools - Darold H. Joseph; Chesleigh N. Keene; Angelina E. Castagno; Pradeep M. Dass; Crystal Macias (SAGE Publishing, 2024)
This article presents the first psychometric validation of the Culturally Responsive Assessment of Indigenous Schooling ( CRAIS) tool, alongside a call for methodological complexity when engaged in research with and in Indigenous contexts. We examined the 23 culturally responsive schooling (CRS) principles underlying the newly created CRAIS tool in independent samples of curriculum units produced by teachers. Of these, 22 principles loaded into two factors. We further investigated the rationale for all 23 items through a review of the literature and robust discussions about the lived experiences of the authors and the Indigenous teachers with whom we work. We suggest that this both/and approach of quantitative and qualitative analysis results in a richer and more nuanced tool, as compared to what one single method would have rendered. Embracing this methodological complexity allows us to both center Indigenous lived experiences and maintain fidelity to the statistical implications of our work.